Impaired cardiac and vascular motion in patients with Takayasu's arteritis: A velocity vector imaging-based study - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (AVES, 2018)
Objective: Takayasu's arteritis (TAK) is a chronic inflammatory vasculitis of the aorta and its major branches. In the present study, we aimed to evaluate the motion of the vascular wall and myocardial contractility by using a novel strain imaging method, velocity vector imaging (VVI), in patients with TAK. We also aimed to compare them with another inflammatory autoimmune disorder, systemic lupus erythematosus (SLE). Methods: We studied 33 patients with TAK, 18 patients with SLE, and 20 age-and sex-matched controls. All participants were subjected to carotid artery Doppler ultrasonography and transthoracic echocardiographic evaluation. VVI analysis was also performed to assess subclinical left ventricular (LV) systolic dysfunction and to determine tissue motion of the common carotid arteries (CCAs). Results: Aortic strain and distensibility were significantly impaired in patients with TAK, while the aortic stiffness and carotid artery stiffness indexes were increased. Aortic distensibility was the only parameter that was decreased among SLE patients. The values of CCA peak longitudinal strain, strain rate, and total longitudinal displacement (TLD) were also impaired in patients with TAK. Peak radial velocity was decreased while time-to-peak radial velocity was increased. In the SLE group, peak longitudinal strain, strain rate, TLD, and peak radial velocity were impaired. LV longitudinal peak systolic strain and strain rate were reduced in patients with TAK. Similarly, we revealed impaired subclinical LV systolic function in patients with SLE. Conclusion: VVI is a novel strain imaging technique with additional value to determine early impairment in vascular and myocardial wall motion in patients with TAK.
Keywords: Takayasu's arteritis; carotid artery; cardiac; strain; velocity vector imaging; REGIONAL MYOCARDIAL-FUNCTION; SYSTEMIC-LUPUS-ERYTHEMATOSUS; LEFT-VENTRICULAR DYSFUNCTION; COMMON CAROTID-ARTERY; SYSTOLIC EXPANSION; STRAIN-RATE; DOPPLER; WALL; CARDIOMYOPATHY; CLASSIFICATION